Children’s Individual Differences in Executive Function and Theory of Mind in Relation to Prejudice Toward Social Minorities - Hoyo, Ángela; Rueda, M. Rosario; Rodríguez-Bailón, Rosa (Frontiers in Psychology, 2019)
Executive function and theory of mind are key cognitive skills for socio-emotional adjustment. Executive function develops considerably between 3 and 7 years of age, and fosters the development of social cognition skills such as theory of mind. Studies with adults have shown a link between executive function and prejudice, as well as between empathy and prejudice. Moreover, the relationship between executive function, cognitive and affective theory of mind and prejudice has barely been studied in children. In this study, we aimed at examining the relationship between individual differences in executive function, cognitive and affective theory of mind and prejudice toward the Romany ethnic minority. We expected a positive association between executive function and theory of mind skills, and a negative association between executive function and prejudice. We also predicted a negative association between theory of mind and prejudice. A total of 86 preschool (5-6 years old, N = 43) and third-grade (8-9 years old, N = 43) children participated in the study. Results showed a negative relationship between executive function and prejudice, as well as between affective theory of mind and prejudice, after controlling for intelligence. Moreover, we found that executive function significantly predicted prejudice. Exploratory correlational analyses suggested age-related differences in the executive function skills underlying prejudice regulation. These findings suggest a distinctive contribution of cognitive and affective components of theory of mind to prejudice, and highlight the central role of executive function in social behavior regulation.